Depression literacy and awareness of psychopathological symptoms during the perinatal period. - Fonseca, Ana (2017)
OBJECTIVE: To characterize women's depression literacy during the perinatal period, including their ability to recognize clinically significant symptoms of depression. DESIGN: A quantitative, cross-sectional, survey design. SETTING: Internet communities and Web sites focused on the topics of pregnancy and motherhood. PARTICIPANTS: A total of 194 women during the perinatal period (32.5% pregnant, 67.5% postnatal) completed the survey; 34.0% had clinically significant psychopathological symptoms. Most women were married/cohabiting (82.0%) and employed (71.8%). METHODS: Women answered self-report questionnaires to assess depression literacy, symptoms of depression, emotional competence, and awareness/recognition of psychopathological symptoms. RESULTS: Women had moderate levels of depression literacy during the perinatal period, with higher literacy levels concerning depression-related characteristics than depression-related treatments. Lower education and lower income were associated with poor depression literacy, whereas prior history of psychiatric problems or treatments was associated with higher levels of depression literacy. An indirect effect through emotional competence in the relationship between depression literacy and awareness/recognition of symptoms was found: women with poor depression literacy tended to have a greater lack of emotional clarity, which negatively affected their symptom awareness and recognition. CONCLUSION: Our results support the need to improve women's mental health literacy during the perinatal period. Education on mental health topics in the context of a trusting relationship with health professionals may contribute to the promotion of women's depression literacy and emotional competence.